Christ in Miguel de Unamuno - García Mateo, Rogelio (Razón y fe, 2022)
The positivist and dissolving rationalism of the nineteenth century took its toll on the student at the University of Madrid, Miguel de Unamuno, making him unable to find an answer to the Christian devotion learned in his native Bilbao, until the crisis of March 1897 made him realize the emptiness of his atheism. This led him to rediscover the religious value of existence, but without incurring in an irrational or fideistic vitalism. Precisely in this lies the originality of his position, which is misunderstood by many: neither bending to the yoke of rationalist logic nor allowing himself to be blindly carried away by the impulses of the heart. Faith and reason must confront and fight each other, because it is through this conflict that a profound reconciliation of both is reached, which find in the mystery of Christ, “true God and true man,” their paradigm of mediation.
Keywords: philosophy; existentialism; atheism; crisis